DIGITAL MARKETPLACES FOR FARM PRODUCTS: BUILDING AN ONLINE PLATFORM FOR YOUTH-DRIVEN AGRIBUSINESS IN NIGERIA - SADIQ MS; SINGH IP; AHMAD MM; SANI BS (Innovare Journal of Agricultural Sciences, 2025)
Digital marketplaces for farm products are transforming agricultural value chains by enabling direct connections between producers and consumers, enhancing market access, and optimizing supply chains, especially in developing regions. This research review explores the potential of digital marketplaces as a tool for empowering youth in agribusiness, analyzing case studies, examining theoretical frameworks such as platform theory and innovation diffusion, and identifying challenges and opportunities for scaling these platforms. The article concludes with recommendations for stakeholders to foster inclusive, youth-led digital agribusiness ecosystems.